“Hudhud of Dinulawan and Bugan at Gonhadan” (Oral Literature of Ifugao Culture) - Batin, Judith (JPAIR Multidisciplinary Research, 2014)
In 2001, UNESCO proclaimed the Ifugao epic hudhud as one of the 19 masterpieces of the oral and intangible heritage of humanity. This study aims to promote greater understanding and of appreciation, and interest in the epics, highest form of oral literature. The analysis is anchored on E. Arsenio Manuel’s theory of the Philippine ethno-epic. A descriptive-qualitative method was used in this study. Immersion, observation and random informal interviews in Ifugao (Kiangan, Asipulo and Lagawe) were employed in gathering and validating data. The narrative structure and characterization of the epic heroes were determined through textual analysis. A contextualist approach in the analysis of the text was utilized to validate the identified Ifugao culture that is still practiced today. The epic reveals the beauty and legacy of the great ancestors of the highland that need to be protected and preserved. This study helps in the preservation of the sacredness of the tradition. Likewise, it also proves that the hudhud is not just used as mere tourist attraction of the local government units and Department of Tourism for economic growth in the hudhud areas. It will also attract more scholars, local and international, to understand and preserve the rich and dying tradition.